Ladybirds (Coleoptera: Coccinellidae) of Iran: 45 new records from 10 provinces - Abdolahi, R.; Nedvěd, Oldřich; Nozari, J. (Akadémiai Kiadó, 2017)
Forty-five records of 28 species of ladybird beetles (belonging to 15 genera, 8 tribes and 6 subfamilies of Coccinellidae) as new for particular provinces in Iran are presented. The ten provinces with new records are Alborz, Golestan, Hamadan, Hormozgan, Kohgiluyeh and Boyer-Ahmad, Mazandaran, North Khorasan, Sistan and Baluchistan, Tehran, and Zanjan.
Keywords: lady beetle; ladybug; distribution; Iran